LncRNA TM1‐3P Regulates Proliferation, Apoptosis and Inflammation of Fibroblasts in Osteoarthritis through miR‐144‐3p/ONECUT2 Axis. Issue 11 (30th September 2022) - Yi, Yangfei; Yang, Ningyin; Yang, Zirui; Tao, Xiaojun; Li, Yufei
Abstract : Objective: This study explores LncRNA TM1‐3P effects on the proliferation, apoptosis, and inflammatory response of fibroblasts in osteoarthritis (OA) and its underlying mechanism. Methods: Bioinformatics was performed to analyze OA disease‐related genes, miRNA profiles, and function. The targeted regulation of LncRNA TM1‐3P and miR‐144‐3p, ONECUT2 and miR‐144‐3p were analyzed by dual luciferase reporter gene assay, RNA Binding Protein Immunoprecipitation (RIP), and RNA pull down. Histopathological morphology of the knee joint was observed by hematoxylin–eosin (HE) and Annona Red O/Fast Green. The expressions of mRNAs and proteins were detected by RT‐qPCR, Western blot, and immunohistochemistry. Unpaired T test was used between groups, and the one‐way analysis of variance of repeated measurement data was applied for multi‐group comparison, following Tukey's post‐test. Results: ONECUT2 and Smurf2 genes were significantly elevated in the osteoarthritis group compared with the normal group ( P  < 0.001, P  < 0.001). Expressions of ONECUT2 and LncRNA TM1‐3P were increased, and expression of miR‐144‐3p was decreased in interleukin (IL)‐1β‐induced human fibroblast synovial cells (hFSCs) (mRNA: 1.06 ± 0.24 vs. 3.29 ± 0.73, proteins: 0.22 ± 0.03 vs. 0.46 ± 0.22, 1.23 ± 0.22 vs. 3.76 ± 0.73, 1.06 ± 0.25 vs. 0.37 ± 0.13, P  < 0.01, P  < 0.001, P  < 0.01, P  < 0.05). Overexpression of miR‐144‐3p down‐regulated the ONECUT2 expression, reduced cell proliferation, promoted apoptosis in hFSCs induced by IL‐1β (mRNA: 0.89 ± 0.14 vs. 0.15 ± 0.01, P  < 0.05; proteins: 0.46 ± 0.01 vs. 0.23 ± 0.01, P  < 0.001; CCK8: 1.88 ± 0.07 vs. 1.65 ± 0.07; P  < 0.05; EDU: 55.82 ± 1.44 vs 40.57 ± 2.24, P  < 0.05; apoptosis: 10.57 ± 0.79 vs 16.36 ± 0.35, P  < 0.0001). Overexpression of LncRNA TM1‐3P up‐regulated the expression of ONECUT2, promoted cell proliferation, and inhibited apoptosis (mRNA: 0.9 ± 0.09 vs 1.94 ± 0.12, P  < 0.05; proteins: 0.61 ± 0.05 vs 0.76 ± 0.03, P  > 0.05; CCK8: 2.07 ± 0.05 vs 2.47 ± 0.06; P  < 0.01; EDU: 52.67 ± 1.17 vs 60.06 ± 3.24, P  < 0.05; apoptosis: 10.57 ± 0.79 vs 16.36 ± 0.35, P  < 0.001), which were reversed by the overexpression of miR‐144‐3p treatment (mRNA: 1.82 ± 0.07 vs 0.31 ± 0.07, P  < 0.0001; proteins: 0.74 ± 0.02 vs 0.35 ± 0.01, P  < 0.01; CCK8: 2.41 ± 0.01 vs 1.67 ± 0.02; P  < 0.0001; EDU: 66.85 ± 2.86 vs 44.68 ± 1.97, P  < 0.0001; apoptosis: 7.19 ± 0.19 vs 13.36 ± 0.53, P  < 0.0001). Silencing LncRNA TM1‐3P attenuated the injury of knee joint tissue, down‐regulated the expression of ONECUT2, Smurf2, IL‐1β, IL‐6, TNF‐α, and improved the expression of Rap1 in rats (0.71 ± 0.04 vs 0.48 ± 0.02, 0.68 ± 0.06 vs 0.36 ± 0.02, 0.74 ± 0.03 vs 0.49 ± 0.04, 0.78 ± 0.01 vs 0.54 ± 0.03, 0.68 ± 0.02 vs 0.4 ± 0.04, 0.24 ± 0.01 vs 0.4 ± 0.03, P  < 0.05, P  < 0.05, P  < 0.05, P  < 0.01, P  < 0.01, P  < 0.05). Conclusion: LncRNA TM1‐3P improved inflammation and damage of knee joints in OA rats through miR‐144‐3p/ONECUT2 axis, providing a new theoretical basis for gene therapy of OA. Abstract : TM1‐3P alleviated synovial tissue damage and inflammation in OA rats. (A, B) Histopathological changes of knee cartilage were observed by HE and Annona Red O/Fast Green staining. (C, D) Immunohistochemistry was used to detect the expression of MMP13, ADAMTS5, Collagen II and Aggrecan in synovial tissue. (E) The expression of ONECUT2, Smurf2 and Rap1 in synovial tissue was detected by Western blot. (F) The expression of IL‐1β, IL‐6 and TNF‐α in synovial tissue was detected by qRT‐PCR and Western blot. * P  < 0.05 vs Sham group, # P  < 0.05 vs LV‐sh‐LncRNA NC group.